2012
DOI: 10.5430/jnep.v2n3p173
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of nurses’ knowledge of genetics

Abstract: Background: Given the current emphasis on genetics as a relatively new topic in the field of mainstream healthcare, it is interesting to note that authors suggested that genetics should be included in nursing curricula almost fifty years ago. Genetics has been important to the role of nurses in specific specialities for some years. However, some studies reported that the current training with respect to genetics for nurses did not enable them to acquire the necessary skills for their work. The aims and objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
1
25
0
11
Order By: Relevance
“…These results can be interpreted that nurses' knowledge about genetics was at the level of "neglected". In line with the results obtained in a previous study conducted that showed that level of knowledge about the genetics nurse well perceived by nurses themselves or directly tested by the researchers showed that low levels of Nurse Media Journal of Nursing, 5 (1), 2015, knowledge (Godino & Skirton, 2012). Based on the phenomenon, it can be seen that the general knowledge of the topic of genetics in nursing students were still lack.…”
Section: Discussionsupporting
confidence: 78%
“…These results can be interpreted that nurses' knowledge about genetics was at the level of "neglected". In line with the results obtained in a previous study conducted that showed that level of knowledge about the genetics nurse well perceived by nurses themselves or directly tested by the researchers showed that low levels of Nurse Media Journal of Nursing, 5 (1), 2015, knowledge (Godino & Skirton, 2012). Based on the phenomenon, it can be seen that the general knowledge of the topic of genetics in nursing students were still lack.…”
Section: Discussionsupporting
confidence: 78%
“…The findings that knowledge, involvement and confidence relating to genetics and nutritional genomics are limited among dietitians mirror results of studies conducted with other non-genetic health professionals such as physicians, nurses, midwives and allied health professionals (Metcalfe et al 2002;Skirton et al 2012;Godino and Skirton 2012;Benjamin et al 2009;Lapham et al 2000;Long et al 2001). Efforts to increase the awareness and competence of health professionals in relation to genetics and genomics have been addressed via multiple approaches.…”
Section: Preparedness Of Health Professionalsmentioning
confidence: 83%
“…[16] Nursing schools and professional organizations must take the lead in preparing the 21st century health professional, in the postgenetic/genomic era, to fully integrate, interpret, and inform patients safely and appropriately about genetic issues, including ethical, legal, social and psychological implications of the information. [17,23,31] However, when exploring the comfort level of pre-licensure nursing students, the education group had lower scores than the control group. Although education clearly had an impact on the scores, the information was not retained over the years, though it tended to increase over time.…”
Section: Discussionmentioning
confidence: 98%
“…[16] Studies exploring nurse faculty members' perceived knowledge of genetics continue to demonstrate the limitation of faculty to teach this content. [22][23][24][25] Based on the current findings of these various studies, continued exploration into the grasp of perceived genetic/genomic of students and their comfort level in integrating this knowledge into their practice and future careers as healthcare professionals is required. A nurse who is prepared to integrate and explain this new discipline will be able to assist "an individual or family in understanding their condition or treatment regimen by answering questions or clarifying information that has been provided by other healthcare professional".…”
Section: Literature Reviewmentioning
confidence: 99%